Machining of nickel based alloys using different cemented carbide tools - Khidhir B.A.; Mohamed B. (2023)
This paper presents the results of experimental work in dry turning of nickel based alloys (Haynes - 276) using Deferent tool geometer of cemented carbide tools. The turning tests were conducted at three different cutting speeds (112, 152, 201and 269 m/min) while feed rate and depth of cut were kept constant at 0.2 mm/rev and 1.5 mm, respectively. The tool holders used were SCLCR with insert CCMT-12 and CCLNR - M12-4 with insert CNGN-12. The influence of cutting speed, tool inserts type and workpiece material was investigated on the machined surface roughness. The worn parts of the cutting tools were also examined under scanning electron microscope (SEM). The results showed that cutting speed significantly affected the machined surface finish values in related with the tool insert geometry. Insert type CCMT-12 showed better surface finish for cutting speed to 201 m/min, while insert type CNGN-12 surface roughness increased dramatically with increasing of speed to a limit completely damage of insert geometer beyond 152 m/min. School of Engineering, Taylor's University College.